2005
DOI: 10.1002/pmic.200401250
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteomics and correlated signaling pathway of the thermophilic bacterium Bacillus stearothermophilus TLS33 under cold-shock stress

Abstract: The thermophilic bacterium Bacillus stearothermophilus TLS33 was examined under cold-shock stress by a proteomic approach to gain a better understanding of the protein synthesis and complex regulatory pathways of bacterial adaptation. After downshift in the temperature from 65 degrees C, the optimal growth temperature for this bacterium, to 37 degrees C and 25 degrees C for 2 h, we used the high-throughput techniques of proteomic analysis combining 2-DE and MS to identify 53 individual proteins including diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The adaptation of G. icigianus to extreme environmental conditions makes its proteins difficult to isolate and separate during a proteomic analysis [ 69 , 70 , 71 ]. For the two-dimensional electrophoresis of proteins from thermophilic bacteria, a technique was developed by taking into account the difficulties with the separation of such bacterial proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The adaptation of G. icigianus to extreme environmental conditions makes its proteins difficult to isolate and separate during a proteomic analysis [ 69 , 70 , 71 ]. For the two-dimensional electrophoresis of proteins from thermophilic bacteria, a technique was developed by taking into account the difficulties with the separation of such bacterial proteins.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that after the temperature downshift from 65°C to 37 ° or 25°C for 2 h, six cold shock-induced proteins were markedly expressed under cold stress, such as glucosyltransferase (TagE), anti-sigma B factor (RsbT), Mrp protein homolog (MrpA), dihydroorthase (PyrC), hydroadenosine phosphosulfate reductase (YbbB) and prespore specific transcriptional activator RsfA (RsfA), whose encoded genes were correlated with the sporulation signaling pathway as shown in Fig. 7A (Topanurak et al, 2005). It was also found that the regulation of this bacterial cell under cold shock could be divided to 2 routes of activation (RsbT, TagE, YbbB and RsbT) and deactivation (MrpA and PyrC).…”
Section: Temperature Stressesmentioning
confidence: 99%